2021
DOI: 10.1007/s13304-021-01173-6
|View full text |Cite
|
Sign up to set email alerts
|

The innate aptitude’s effect on the surgical task performance: a systematic review

Abstract: Surgery is known to be a craft profession requiring individuals with specific innate aptitude for manipulative skills, and visuospatial and psychomotor abilities. The present-day selection process of surgical trainees does not include aptitude testing for the psychomotor and manual manipulative skills of candidates for required abilities. We aimed to scrutinize the significance of innate aptitudes in surgical practice and impact of training on skills by systematically reviewing their significance on the surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Surgical education has traditionally transferred from experienced surgeons (high volume centers) to trainees (low volume centers and young surgeons) [ [42] , [43] , [44] ]. However, the H&S offers a paradigm change in surgical education: the Hub offers mentorship, ensuring standardization of training, while spoke unites benefit of huge cohort of patients and hands-on clinical experience [ 13 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical education has traditionally transferred from experienced surgeons (high volume centers) to trainees (low volume centers and young surgeons) [ [42] , [43] , [44] ]. However, the H&S offers a paradigm change in surgical education: the Hub offers mentorship, ensuring standardization of training, while spoke unites benefit of huge cohort of patients and hands-on clinical experience [ 13 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…El Boghdady M & Ewalds-Kvist BM (2021), in their systematic review, compare groups that included students with a high level of innate aptitude and another with a low level of innate fitness and concluded that fitness plays a significant role in learning advanced skills, which leads us to believe that this innate aptitude can have been reflected in some of the surgeons in training [40].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, others have found improved results with training [ 31 , 32 ], but to date few studies have been conducted [ 32 ]. A recent review suggested that videogaming did not increase the VSA [ 33 ]. A multitude of different VSA tests have been used in previous studies, which could possibly explain conflicting results to date [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study did not find manual dexterity to be predictive of laparoscopic performance, though previous studies have shown promising results [ 17 , 39 , 40 ]. Other background factors have also been suggested having an impact on laparoscopic performance, such as sex, playing musical instrument, and previous laparoscopic training [ 18 , 33 ]. Louridas et al found previous laparoscopic experience to be the only background factor predictive of baseline laparoscopic skill [ 18 ].…”
Section: Discussionmentioning
confidence: 99%